The Ericsson Corporate Trademark Book : The Brand as a strategic asset - Urde, Mats; Melin, Frans (The Ericsson Corporate Trademark Book, 1999)
HAVING STRONG BRANDS is a key to our success. One of our most important tasks for the future is therefore strengthening the Erisson brand. Our ambition is to further develop Ericsson – a brand that represents and projects reliability. This is a fundamental prerequisite if we are to increase our collective competitiveness, ability to grow, and profitability. 1) The Ericsson Trademark Book: 2) Trademarks at Ericsson 3) The Brand as a strategic asset 4) Trademark problems and how to avoid them
Keywords: trademark; intelectual property; Strategic assets; Strategic Assets